2016
DOI: 10.1007/s10603-016-9333-9
|View full text |Cite
|
Sign up to set email alerts
|

Regime Market Performance Analysis: Informing European Consumer Policy

Abstract: The Single Market of the European Union has progressed during recent decades to encompass more than 500 million consumers in 28 EU Member States and adjoining countries. During the same period, consumer issues have received growing policy interest and policy measures have been put in place to harmonize the Single Market, that is, to make national markets more alike. Yet, in order to provide policy measures that promote desirable market outcomes, the considerable challenge of understanding differences in the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Although these directives have narrowed the Member States' available options for setting their own consumer policy, they still leave some possibilities for the Member States to go further in their national level of consumer protection. Consequently and notwithstanding the efforts of the European Commission to align consumer protection in the Member States, current research has shown that national consumer policy approaches still differ (Cafaggi and Micklitz 2009;Repo and Timonen 2017;Wind 2016).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Although these directives have narrowed the Member States' available options for setting their own consumer policy, they still leave some possibilities for the Member States to go further in their national level of consumer protection. Consequently and notwithstanding the efforts of the European Commission to align consumer protection in the Member States, current research has shown that national consumer policy approaches still differ (Cafaggi and Micklitz 2009;Repo and Timonen 2017;Wind 2016).…”
mentioning
confidence: 99%
“…Comparative studies of consumer policy in Europe have used a regime approach in seeking to identify similarities and differences of consumer policy models between groups of countries (Cafaggi and Micklitz 2009;Cseres 2005;Micklitz 2003;Repo and Timonen 2017;Trumbull 2006a, b). Despite different research interests and scientific perspectives, all of these studies found consumer policy regimes, such as a Scandinavian regime consisting of Denmark, Finland, and Sweden or an East European regime consisting of all East European Member States.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, also Geels et al (2016) suggest scholars should address multiple niche and regime innovations jointly. The concept of regime used in the MLP resembles those used in other contexts such as in international politics and economy to describe arrangements and commonalities (Krasner 1982, Hall and Soskice 2001, Holtz et al 2008, Repo and Timonen 2017, but it is applied in a sociotechnical setting.…”
Section: Research Frame Of the Studymentioning
confidence: 99%